(untitled) (Damascus University Journal of agriculture sciences, 2025)
The study aimed to monitor the atmospheric load of pollen of olive trees (Olea europaea L) that may cause allergies to humans. The daily and seasonal changes of airborne pollen was monitored and its concentration was linked to the basic weather factors (precipitation, temperature and wind speed). The air was sampled in Abu Jerash , Damascus during the spring seasons of 2018 and 2019 using a portable battery-powered volumetric trap that was devised and executed for this purpose. Sampling was conducted five times a day (9, 11,14,17,20 h), at a height of 1.5 m above the ground. The results indicate that the concentration curve of olive pollen grains was different between the two seasons, as it recorded in the first season the highest concentration of pollen during the first half of April until late May, and it decreased during June, to disappear and absent later. The actual pollen season extended 29 days, and the peak was in the middle of April. During the second season of 2019, the pollen release period was 41 days, and the density began to decrease from the first third of May until its end. A clear effect of climate factors was observed on the density of pollen in the air. The effect was positive for the high temperatures that influenced the maturation and opening of flowers and the release of pollen, while rainfall had an opposite effect, as the number of pollen grains decreased during and after rainy days, and the concentration reached the lowest recorded values. Wind speed played a positive role in increasing the number and spread of trapped pollen grains